1975
DOI: 10.1002/1097-0142(197510)36:4<1363::aid-cncr2820360427>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Papillary meningioma: A malignant variant of meningioma

Abstract: A series of 17 menitlgiomas histologically characterized by a papillary pattern is reported. This pattern was invariably associated with other histologic features of malignancy. The tumors often displayed aggressive clinical behavior marked by a high rate of local recurrence or the development of distant metastases. A relatively large proportion occurred in children. It is suggested that this variant of meningioma is sufficiently characteristic to justify its separation as a distinct clinicopatholagic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(49 citation statements)
references
References 14 publications
2
47
0
Order By: Relevance
“…1,3,4,[6][7][8][9][11][12][13][14]16,19) The risk of CSF dissemination of this tumor is not clear. Twelve of these 18 patients had undergone two or more surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,[6][7][8][9][11][12][13][14]16,19) The risk of CSF dissemination of this tumor is not clear. Twelve of these 18 patients had undergone two or more surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical behavior of PM, the study by Ludwin et al (13) indicated that these tumors frequently display an aggressive clinical behavior, which is marked by a high rate of local recurrence and/or development of distant metastases. Jiang et al (16) reported a case of intraparenchymal PM of the brainstem.…”
Section: A B C Dmentioning
confidence: 92%
“…In addition, 25% of the tumors assessed occurred in patients within the first two decades of their life, with a slightly increased incidence in females (female to male ratio, 3:2). Furthermore, Ludwin et al (13) identified that a relatively large proportion of PM cases in their study (8/17 patients) occurred in children, while Pasquier et al (14) reported seven cases of PM that occurred in patients between the ages of 21 and 69 years.…”
Section: A B C Dmentioning
confidence: 99%
“…The single most important factor in the clinical outcome of meningiomas is probably the localisation and resectability of the tumour [18]. However, some histological findings have been associated with a higher risk of recurrences [15,16,21]: invasion of the underlying brain tissue, a high degree of cellularity and cytological features of malignancy, including aneuploidy, mitotic figures, large prominent nucleoli and the presence of necrotic areas [5,7,9,22].…”
Section: Introductionmentioning
confidence: 99%